Caracterización del programa de alojamiento estudiantil de la universidad de los andes y la universidad nacional (2022)
Hotels are infrastructures of a private order but that comply in one way or another way a well-known objective and it is that the use that is given to them is public since it houses people of different places of origin; for example, university housing seeks to provide facilities to students who require a place to stay while they are in their stage of studies that give them peace of mind to be able to successfully complete their training, since as citation Writing Education, El tiempo. (2021) “in Colombia, each year more than 98,000 young people who graduate from high school migrate to other cities to get into university, and of these the 72% focus on five main capitals in the country” (par.1) of which Bogotá hosts more than a half. As mentioned in said article “of the 98,604 high school graduates from the school in in 2018 who migrated to immediately continue their higher education studies in In 2019, 72.38% went to higher education institutions in Bogotá, Medellín, Barranquilla, Cali and Bucaramanga” (Education Editorial Office, El tiempo, 2021, para. 2). Being Bogotá the city chosen by the largest number of students with 55,998, which represents the 56.79% of educational migration in the nation. The offer of higher education has been concentrated mostly in the main capital cities of the departments in the country, according to Ospina Londoño, M., Canavire, G., Bohorquez, S., & Cuartas, D. (2015). Expansion of higher education and its effects on enrollment and migration: evidence from Colombia. Q. 4. “migration can be interpreted as result of an inefficient allocation of the offer in higher education programs”, if a student in his place of origin does not have the offer he is looking for, he has no other option than 5 migrate Next, it is possible to observe as an example the displacement of students from different departments of the country to the main cities